2015
DOI: 10.1039/c4cc09498k
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced vibrational spectroscopic evidence for an alternative DNA-independent redox activation of endonuclease III

Abstract: Surface enhanced vibrational spectro-electrochemistry of endonuclease III provides direct evidence that the [4Fe-4S] cluster is responsible for the enzyme redox activity, and that this process is not exclusively DNA-mediated, as currently proposed. We report the first surface enhanced resonance Raman spectrum of a [4Fe-4S] 2+ cluster containing enzyme.Deinococcus radiodurans is an extremely radiation and desiccation resistant bacterium, which can withstand 200-fold higher irradiation doses than other bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
6
17
1
Order By: Relevance
“…Spectra were measured with 413 nm excitation at 77 K using 1.5 and 8 mW in the SERR and RR experiments, respectively.Reproduced from Ref. [11] with permission from The Royal Society of Chemistry…”
Section: Rr Spectroscopy Of Fe–s Proteins and Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectra were measured with 413 nm excitation at 77 K using 1.5 and 8 mW in the SERR and RR experiments, respectively.Reproduced from Ref. [11] with permission from The Royal Society of Chemistry…”
Section: Rr Spectroscopy Of Fe–s Proteins and Enzymesmentioning
confidence: 99%
“…The large body of work on synthetic clusters and simple monocluster containing proteins, mainly those involved in electron transfer (ET) (vide infra 3.1) led to a well-established assignment of their vibrational spectra and paved the way to studies of more complex systems [ 3 10 ]. More recently, RR has been shown to be capable of providing fine details on transient processes that involve Fe–S proteins [ 3 10 ], and has been extended to surface enhanced RR (SERR) to characterize immobilized Fe–S enzymes interacting with physiological substrates [ 11 , 12 ]. Here, we aim to present an overview of RR studies on structurally and functionally different Fe–S proteins, highlighting the type of information that can be extracted from RR spectra and in parallel, discuss their thermodynamic properties (e.g., reduction potential).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that carboxylic acid monolayers had a similar activating effect as DNA, although, in contrast with the above model, they identified the relevant couple as the [4Fe4S] 2+/+ rather than the [4Fe4S] 3+/2+ couple (16). With respect to the latter point, the high potential of the reversible DNA-bound signal on both gold and HOPG, EPR spectroscopy of oxidized DNA bound EndoIII and MutY, and the observation of both couples in the expected potential regimes on HOPG support the original [4Fe4S] 3+/2+ assignment (6,8,15).…”
Section: Introductionmentioning
confidence: 85%
“…Initially it was suggested to possess only a structural role (Fu et al, 1992) and later that it is involved in redox regulated DNA mediated signaling (Boal et al, 2005). Recently the cluster was also proposed to act as a redox centre that could be activated by charged entities other than DNA, suggesting a potential role in processes related to the organism's defense against reactive oxygen species (Moe et al, 2015). There is no evidence so far that the cluster may be directly involved in the catalytic process.…”
Section: The Iron Sulphur Cluster Loop Is Conservedmentioning
confidence: 97%